Case report: subacute thyroiditis after receiving SARS-CoV-2 vaccine, maybe not only adjuvants - Huang, Yizhou; Chen, Xingyu; Wang, Qing; Lei, Xiaowei; Zhang, Lili (Frontiers in Medicine, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) induced the new coronavirus disease 2019 (COVID-19) pandemic worldwide. SARS-CoV-2 vaccines are designed to control the transmission of the disease. However, post-vaccination subacute thyroiditis (SAT) also appears with increase vaccination rate. Three cases of SAT after SARS-CoV-2 vaccines are described in this study. We have reported the patients’ clinical symptoms, laboratory tests, and thyroid imaging. Tests for COVID-19 were all negative, and the patients did not report thyroid-related diseases, autoimmune diseases, or preceding upper respiratory system infections in their medical history. Three female patients showed neck pain on physical examination. The laboratory test results and imaging findings were consistent with the diagnostic criteria of SAT. The patients were carried out a standardized treatment according to their symptoms, and we closely followed up their response to the treatment. Clinicians must be aware of the possibility of SAT after receiving the vaccines and make timely therapy.